The prevalence of drug-resistant tuberculosis (DR-TB) and risk factors for unfavourable treatment outcomes in Selangor and Wilayah Persekutuan Kuala Lumpur (WPKL), Malaysia - Zaman, Mohd Fahmin Kamarul (2023)
Introduction: Drug-resistant TB (DR-TB) is a global public health burden that causes high morbidity and mortality among the population. The increase in DR-TB cases has become evident in Malaysia over the past few years. Effective and systematic treatment can save lives; however, unfavourable treatment outcomes are a barrier. This study aims to determine the prevalence rate and the associated factors with unfavourable treatment outcomes among DR-TB patients in Selangor and WPKL from 2016 to 2020. Methods: This study has two components: prevalence rate and case-control analysis, utilizing secondary data obtained from the National Tuberculosis Surveillance Database (MyTB). All reported DR-TB cases in MyTB between 2016 and 2020 that met the study criteria were analysed. The case group consists of 181 DR-TB cases with unfavourable treatment outcomes, whereas the control group consists of 222 DR-TB cases with favourable treatment outcomes. Multiple logistic regression was used for data analysis. Results: There was an increment in the prevalence rate of DR-TB cases in Selangor and WPKL from 2016 to 2020, from 0.31 to 1.83 per 100,000 population. DR-TB cases with unfavourable treatment outcomes accounted for 42%. The significant factors associated with unfavourable treatment outcomes among DR-TB cases were male (AdjOR 2.38; 95% CI: 1.44, 3.94), single and divorced (AdjOR 1.61; 95% CI: 1.03, 2.49), receive no formal education (AdjOR 3.09; 95% CI: 1.49, 6.41), HIV positive (AdjOR 2.87; 95% CI: 1.40, 5.87), DR-TB category for RR- TB (AdjOR 3.34; 95% CI: 1.90, 5.86) and MDR/ Pre-XDR/ XDR-TB (AdjOR 2.57; 95% CI: 1.52, 4.33). Conclusion: Therefore, unfavourable treatment outcomes among DR-TB cases should be tackled through holistic public health interventions involving commitment from all stakeholders. Future studies need to explore other parameters as well as drive efforts to start capturing additional significant variables in the surveillance database for all TB cases.